Rapid efficient synthesis and characterization of silver, gold, and bimetallic nanoparticles from the medicinal plant plumbago zeylanica and their application in biofilm control - Salunke, Gayatri R.; Ghosh, Sougata; Kumar, R. J. Santosh; Khade, Samiksha; Vashisth, Priya; Kale, Trupti S.; Chopade, Snehal; Pruthi, Vikas; Kundu, Gopal; Bellare, Jayesh R.; Chopade, Balu Ananda (International Journal of Nanomedicine, 2014)
Background: Nanoparticles (NPs) have gained significance in medical fields due to their high surface-area-to-volume ratio. In this study, we synthesized NPs from a medicinally important plant - Plumbago zeylanica. Materials and methods: Aqueous root extract of P. zeylanica (PZRE) was analyzed for the presence of flavonoids, sugars, and organic acids using high-performance thin-layer chromatography (HPTLC), gas chromatography-time of flight-mass spectrometry (GC-TOF-MS), and biochemical methods. The silver NPs (AgNPs), gold NPs (AuNPs), and bimetallic NPs (AgAuNPs) were synthesized from root extract and characterized using ultraviolet-visible spectra, X-ray diffraction (XRD), energy-dispersive spectrometry (EDS), transmission electron microscopy (TEM), and dynamic light scattering (DLS). The effects of these NPs on Acinetobacter baumannii, Staphylococcus aureus, and Escherichia coli biofilms were studied using quantitative biofilm inhibition and disruption assays, as well as using fluorescence, scanning electron microscopy, and atomic force microscopy. Results: PZRE showed the presence of phenolics, such as plumbagin, and flavonoids, in addition to citric acid, sucrose, glucose, fructose, and starch, using HPTLC, GC-TOF-MS, and quantitative analysis. Bioreduction of silver nitrate (AgNO3) and chloroauric acid (HAuCl4) were confirmed at absorbances of 440 nm (AgNPs), 570 nm (AuNPs), and 540 nm (AgAuNPs), respectively. The maximum rate of synthesis at 50 degrees C was achieved with 5 mM AgNO3 within 4.5 hours for AgNPs; and with 0.7 mM HAuCl4 within 5 hours for AuNPs. The synthesis of AgAuNPs, which completed within 90 minutes with 0.7 mM AgNO3 and HAuCl4, was found to be the fastest. Fourier-transform infrared spectroscopy confirmed bioreduction, while EDS and XRD patterns confirmed purity and the crystalline nature of the NPs, respectively. TEM micrographs and DLS showed about 60 nm monodispersed Ag nanospheres, 20-30 nm Au nanospheres adhering to form Au nanotriangles, and about 90 nm hexagonal blunt-ended AgAuNPs. These NPs also showed antimicrobial and antibiofilm activity against E. coli, A. baumannii, S. aureus, and a mixed culture of A. baumannii and S. aureus. AgNPs inhibited biofilm in the range of 96%-99% and AgAuNPs from 93% to 98% in single-culture biofilms. AuNPs also showed biofilm inhibition, with the highest of 98% in S. aureus. AgNPs also showed good biofilm disruption, with the highest of 88% in A. baumannii. Conclusion: This is the first report on rapid and efficient synthesis of AgNPs, AuNPs and AgAuNPs from P. zeylanica and their effect on quantitative inhibition and disruption of bacterial biofilms.
Keywords: AgAuNPs; AgNPs; AuNPs; biofilm inhibition and disruption; GC-TOF-MS; P. zeylanica

Vivo wound healing performance of halloysite clay and gentamicin-incorporated cellulose ether-PVA electrospun nanofiber mats - Wali, Ashwini; Gorain, Mahadeo; Inamdar, Satish; Kundu, Gopal; Badiger, Manohar V. (ACS Applied Bio Materials, 2019)
Wound healing is a dynamic and complex process that requires a suitable environment to enhance the rapid healing process. In this context, fabrications of nanofibrous materials with antibiotic and antibacterial properties are becoming extremely important. In this present work, we report on the fabrication and characterization of electro-spun cellulose ether-PVA nanofiber mats loaded with halloysite clay (HNT) and gentamicin sulfate (GS) for faster wound healing applications. The morphology of nanofiber mats was examined by SEM and TEM. The average diameter of the nanofiber mats were in the range of 325 ± 30 nm. The physicochemical characterizations were done by FT-IR and XRD, which reveal the presence of HNT and GS into the nanofibers. The incorporation of halloysite gave good mechanical strength to the nanofiber mats. Swelling studies indicated the hydrophilicity of the mats. In vitro studies revealed that HNTs are nontoxic to L929 fibroblast cells and also promote cell growth and proliferation. The antibacterial property of HNT was also studied. The slow release of GS from the nanofiber mats was observed for a period of 18 days. The in vivo wound healing studies on the wistar rats for 21 days revealed the wound healing faster within 2 weeks by the incorporation of HNT and GS into the nanofiber mats and hence these nanofiber mats show great potential in acute and chronic wound healing applications.

Silver nanoparticles in electrospun ethyl hydroxy ethyl cellulose-PVA Nanofiber: synthesis, characterization and wound dressing applications - Wali, Ashwini; Gorain, Mahadeo; Kundu, Gopal; Badiger, Manohar (Carbohydrate Polymer Technologies and Applications, 2024)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Electrospinning is a simple, cost-effective technique and a reproducible process for both synthetic and <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/natural-polymer" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about natural polymers from ScienceDirect's AI-generated Topic Pages">natural polymers. It is found to be an attractive tool for various applications in biomedical engineering, filtration, protective clothing, catalysis reactions and sensors. Non-ionic cellulose ethers namely Ethyl Hydroxy <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/ethyl-cellulose" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about Ethyl Cellulose from ScienceDirect's AI-generated Topic Pages">Ethyl Cellulose (EHEC) is an important <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polysaccharide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about polysaccharide from ScienceDirect's AI-generated Topic Pages">polysaccharide which is non-toxic, biocompatible and biodegradable and finds applications as thickening/rheology control agents in paints, cosmetics, detergents, oil recovery and also in the biomedical area. Poly (vinyl alcohol) (PVA) is a semi-crystalline <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/hydrophilic-polymers" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about hydrophilic polymer from ScienceDirect's AI-generated Topic Pages">hydrophilic polymer which is highly biocompatible and non-toxic having good thermal and mechanical properties and also high water solubility. Silver shows powerful antimicrobial activity and is non-toxic. It has been used to cure severe burns and chronic ulcers for many decades and is extensively used as an additive in various fields like prostheses, burn treatment, catheters, vascular grafts, dental resin components, ion exchange fibers, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/stainless-steel" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about stainless steel from ScienceDirect's AI-generated Topic Pages">stainless steel materials, human skin and coating of <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/medical-device" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about medical devices from ScienceDirect's AI-generated Topic Pages">medical devices. In the present work, EHEC/PVA <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers embedded with silver <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanoparticles from ScienceDirect's AI-generated Topic Pages">nanoparticles (AgNPs) are studied for their <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/antibacterial-activity" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about antibacterial activity from ScienceDirect's AI-generated Topic Pages">antibacterial activity using both gram positive and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/gram-negative-bacterium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about gram negative bacteria from ScienceDirect's AI-generated Topic Pages">gram negative bacteria. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers show increase in <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/tensile-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about tensile properties from ScienceDirect's AI-generated Topic Pages">tensile properties with the addition of silver nano-particles. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/silver-nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about AgNPs from ScienceDirect's AI-generated Topic Pages">AgNPs embedded EHEC/PVA nanofiber mats having 0.5% AgNPs were found to enhance the <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound-healing" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wound healing from ScienceDirect's AI-generated Topic Pages">wound healing with no scar formation in <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wistar-rat" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wistar rats from ScienceDirect's AI-generated Topic Pages">wistar rats. The biological <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vitro<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vivo<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> studies support the potential of EHEC based <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers as excellent bio-materials for the treatment of severe burns and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wounds from ScienceDirect's AI-generated Topic Pages">wounds. To the best of our knowledge, this is the first report on the electrospinning of EHEC/PVA nanofibers for wound healing applications.